Study on the Energy and Exergy of a Biomass-Assisted Recirculating Mixed-Flow Dryer Utilized for Drying Paddy - Yahya, Muhammad; Wardianto, Dedi (IJIMCE : International Journal of Innovation in Mechanical Construction and Energy, 2024)
The performance of a biomass-assisted recirculating mixed-flow dryer for drying paddy (Oryza sativa L.) was thoroughly assessed. The dryer system comprises a biomass furnace, drying column, vibratory feeder, bucket elevator, and blower. In the experimental setup, the drying time required to reduce the moisture content of paddy from 20.90% (wet basis) to 13.30% (wet basis) was measured at 4.5 hours. During this period, the average air temperature was recorded at 78.15 °C, accompanied by an average relative humidity of 8.55%. The observed drying rate ranged from 1.688 to 18.126 kg/h, with an average value of 7.792 kg/h. Further analysis revealed that the specific moisture evaporation rate (SMER) and specific energy consumption (SEC) varied between 0.122 and 1.308 kg/kWh, and 0.806 and 8.657 kWh/kg, respectively. The corresponding average values were 0.562 kg/kWh for SMER and 4.119 kWh/kg for SEC. The thermal efficiency of the dryer, along with exergy efficiency, demonstrated a range of 7.82% to 83.99% and 15.28% to 25.64%, respectively. The average values for thermal efficiency and exergy efficiency were calculated as 36.11% and 19.46%. Meanwhile, the efficiency of the biomass furnace ranged from 70.63% to 87.70%, with an overall average efficiency of 79.53%.